Use of Participant-Generated Photography in a Research Contribution Course - MaryEllen Thompson PhD, OTR/L (Scholarworks @ WMU, 2013)
This paper describes the use of small, qualitative studies focused on interviews done with participant- generated photographs as an effective and efficient way of teaching research to entry-level masters students. A comparison of using time-use diaries vs. participant-generated photography is presented to explicate the research process and demonstrate the advantages of using photography, including ease of data collection and data sharing. Over a three-year period of using participant-generated photographs as a guide for semi- structured interviews, students have consistently expressed enjoyment of the research process and increased empathy with their research participants.